"Differentiated citizenship" and the persistence of informal rural credit systems in Amazonia. (October 2015) - Mathews, Mason Clay; Schmink, Marianne
Graphical abstract: Socioeconomic continuity and change in Lábrea's riverine communities. Highlights: Informal rural credit (aviamento) persists in Amazonia since colonial times. Over 100 interviews with riverine inhabitants and traders in Lábrea, 2008–2009. Isolation and seasonality cause dependence on river traders, lacking alternatives. Traders provide long-term credit, with less enforcement power and fewer customers. Differentiated citizenship limits access by rural Amazonians to alternative credit. Abstract: In the Brazilian Amazon, the long-distance river trading system known as aviamento has linked commodity producers in remote areas to markets in urban centers since the colonial period. Based on a case study from the rural municipality of Lábrea, this article explores continuities and changes in river trading from the point view of riverine residents and river traders. Geographic isolation and seasonal productive needs continued people's dependence on river traders in 2008–2009, but they had greater choices due to increased access to information, mobility, and alternate markets. Expanded citizenship rights provided access to the vote and to education and other government services, but in a "differentiated" manner that still excluded many rural Amazonians. Given that agroindustry is currently the economic focus for Amazonian development, instead of forest product extraction, these rural producers continued to be forced to rely on informal river traders to meet their needs.